2021
DOI: 10.1155/2021/6632719
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms of Paternal Stress in Offspring Development and Diseases

Abstract: The major biological function of the sperm cell is to transmit the paternal genetic and epigenetic information to the embryo as well as the following offspring. Sperm has a unique epigenome. An increasing body of epidemiological study supports that paternal stress induced by environmental exposures and lifestyle can modulate the sperm epigenome (including histone modification, DNA methylation, and noncoding RNA expression), sperm-egg fusion, embryo development, and offspring health. Based on the existing liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…Recent studies suggested that maternal and paternal exercise may affect the metabolic health in adult offspring (Zheng et al, 2020) and sperm epigenome can be epigenetically modified by environmental factors and the health of the offspring can be affected by the transgenerational passage of the modified epigenome (Xu et al, 2021). Metformin may regulate epigenetic modifications (Menendez, 2020) and these have been considered as one of the mechanisms explaining the beneficial effects of metformin on the prevention of cancer (Cuyàs et al, 2021) and aging (Menendez, 2020).…”
Section: Metformin May Adversely Affect Sexual Functionsmentioning
confidence: 99%
“…Recent studies suggested that maternal and paternal exercise may affect the metabolic health in adult offspring (Zheng et al, 2020) and sperm epigenome can be epigenetically modified by environmental factors and the health of the offspring can be affected by the transgenerational passage of the modified epigenome (Xu et al, 2021). Metformin may regulate epigenetic modifications (Menendez, 2020) and these have been considered as one of the mechanisms explaining the beneficial effects of metformin on the prevention of cancer (Cuyàs et al, 2021) and aging (Menendez, 2020).…”
Section: Metformin May Adversely Affect Sexual Functionsmentioning
confidence: 99%
“…Furthermore, paternal stress can impact the health of offspring through genetic inheritance, particularly by altering the sperm epigenome. This includes modifications in DNA methylation, histone modifications, sncRNAs, and sncRNAs‐associated alterations 49 . Importantly, paternal stress might also indirectly affect the health outcomes of offspring by influencing maternal investment in their offspring 50 .…”
Section: Discussionmentioning
confidence: 99%
“…This includes modifications in DNA methylation, histone modifications, sncRNAs, and sncRNAsassociated alterations. 49 Importantly, paternal stress might also indirectly affect the health outcomes of offspring by influencing maternal investment in their offspring. 50 However, these mechanistic pathways are less well established in humans and should be explored further to establish the first instigators of immune activation in diverse maternal states.…”
Section: F I G U R Ementioning
confidence: 99%
“…Epigenetic modification, especially DNA methylation, plays an important role in determining the differentiation potential of mammalian cells and ensuring the normal development. The methylation changes of a specific gene in the parent sperm cannot directly lead to the defective phenotype of the offspring, but it is undeniable that the methylation of CpG islands affects a series of cascade gene expressions, resulting in abnormal gene crossover network expression [68]. The potential roles of epigenetic processes in the progress of sperm function and male fertilization were studied by many researchers.…”
Section: Aberrant Sperm's Epigenetic Modificationsmentioning
confidence: 99%
“…Sperm histones are involved in chromatin conformation and gene expression through various posttranslational modifications. Modification of sperm histones may influence the large scale demethylation wave after fertilization, altering the expression of offspring genes [68].…”
Section: Disrupted Sperm's Histone Marksmentioning
confidence: 99%